New drugs and emerging therapeutic targets in the endothelin signaling pathway and prospects for personalized precision medicine - Davenport, A P; Kuc, R E; Southan, C; Maguire, J J (Physiological research, 2018)
During the last thirty years since the discovery of endothelin-1, the therapeutic strategy that has evolved in the clinic, mainly in the treatment of pulmonary arterial hypertension, is to block the action of the peptide either at the ET(A) subtype or both receptors using orally active small molecule antagonists. Recently, there has been a rapid expansion in research targeting ET receptors using chemical entities other than small molecules, particularly monoclonal antibody antagonists and selective peptide agonists and antagonists. While usually sacrificing oral bio-availability, these compounds have other therapeutic advantages with the potential to considerably expand drug targets in the endothelin pathway and extend treatment to other pathophysiological conditions. Where the small molecule approach has been retained, a novel strategy to combine two vasoconstrictor targets, the angiotensin AT(1) receptor as well as the ET(A) receptor in the dual antagonist sparsentan has been developed. A second emerging strategy is to combine drugs that have two different targets, the ET(A) antagonist ambrisentan with the phosphodiesterase inhibitor tadalafil, to improve the treatment of pulmonary arterial hypertension. The solving of the crystal structure of the ET(B) receptor has the potential to identify allosteric binding sites for novel ligands. A further key advance is the experimental validation of a single nucleotide polymorphism that has genome wide significance in five vascular diseases and that significantly increases the amount of big endothelin-1 precursor in the plasma. This observation provides a rationale for testing this single nucleotide polymorphism to stratify patients for allocation to treatment with endothelin agents and highlights the potential to use personalized precision medicine in the endothelin field.
Keywords: nemoci cév; receptory endotelinů; signální transdukce; individualizovaná medicína; Amino Acid Sequence; Receptors, Endothelin; Endothelin Receptor Antagonists; Vascular Diseases; Signal Transduction; peptidové fragmenty; Drug Delivery Systems; Animals; lidé; objevování léků; Humans; zvířata; Endothelins; antagonisté endotelinového receptoru; sekvence aminokyselin; Drug Discovery; Precision Medicine; Peptide Fragments; lékové transportní systémy; endoteliny